Analysis of Transparency and Accountability in the Management of School Operational Assistance (BOS) Funds at UPT SD Negeri 82 Barammamase, Takalar Regency - Hariyanti Arung; Sahade; Samsinar (PT. Maju Malaqbi Makkarana, 2026)
This study discusses the transparency and accountability of School Operational Assistance (BOS) fund management at UPT SD Negeri 82 Barammamase in Takalar Regency. The research problem focuses on the implementation of transparency and accountability principles in BOS fund management, starting from planning, implementation, reporting, to accountability. The purpose of this study is to analyze the implementation of transparency and accountability principles in BOS fund management and identify the influencing factors. This study uses a descriptive qualitative approach with data collection techniques through interviews and documentation. Data analysis was carried out using the Miles and Huberman model through data collection, data reduction, data presentation, and conclusion drawing. The results show that BOS fund management at UPT SD Negeri 82 Barammamase has implemented transparency and accountability principles through RKAS preparation, bookkeeping, reporting, and publication of BOS fund usage reports to the public